EFFECT OF DIABETES CARE (DM CARE) ON ANXIETY AND BLOOD GLUCOSE LEVELS DIABETES MELITUS PATIENTS - Rosaline, Mareta Dea; Tobing, Duma Lumban; Anggraeni, Diah Tika (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder commonly associated with physical and psychological complications, including anxiety. Optimal diabetes management requires effective self-care management, which can be enhanced through structured Diabetes Self-Management Education (DSME). The integration of digital health technology, such as mobile-based educational applications, offers a promising strategy to support diabetes management in primary healthcare settings. This study aimed to determine the effect of the Diabetes Care (DM Care) application on anxiety levels and blood glucose levels among patients with T2DM. A quantitative pre experimental study with a one-group pretest–posttest design was conducted at Limo Primary Health Center, Grogol Subdistrict, Depok City. A total of 40 patients with T2DM were recruited using consecutive sampling. The intervention consisting of DSME is delivered through an Android-based DM Care application . Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS), and blood glucose levels were assessed as random blood glucose using a glucometer. The data were analyzed using the Wilcoxon Signed Rank Test with a significance level of p < 0.05. The results showed a significant reduction in anxiety levels and blood glucose levels following the intervention. The mean anxiety score decreased from 30.40 to 7.50, while the mean random blood glucose level decreased from 213.88 mg/dL to 127.88 mg/dL (p = 0.000). In conclusion, the DM Care application significantly reduced anxiety levels and blood glucose levels among patients with T2DM and may serve as an effective digital nursing intervention to improve self-care management and clinical outcomes in primary healthcare settings